Weak Dissipative Structure for Compressible Navier-Stokes Equations (Communications in Mathematical Research, 2021)
This paper concerns the Cauchy problem for compressible Navier-Stokesequations. The weak dissipative structure is explored and a new proof for the classicalsolutions are shown to exist globally in time if the initial data is sufficiently small.
Keywords: compressible Navier-Stokes equation; global existence; weak dissipation; small initial data.